REKOMENDASI TERBAIK UNTUK PERHITUNGAN GAJI KARYAWAN PADA UKM XYZ: ADHERED ATAU OVERLAPPING? - Rizki Alrafi, Muhammad Daffa; Haq, Anaksya; Fernando, Felix; Syawalia Zahra, Fathia; Kartika, Lindawati; Prabu Arya Aviantara, Rayvaldo (PT Naureen Digital Education, 2024)
The role of Small Medium Enterprise (SMEs) is very large for Indonesia's growth. The contribution of SMEs to GDP also reached 60.5 percent and to labor absorption was 96.9 percent of national labor absorption. However, the issue of ideal salaries is still a problem for SMEs in Indonesia, especially due to the influence of certain conditions, both environmental and internal. One of the SMEs that is facing problems with the compensation system is SME XYZ. The aim of this research is to analyze and determine compensation that is in accordance with ideal job grading in UKM XYZ. Data collection in this research was carried out through interviews with the owners of UKM XYZ in February 2024. The data processing methods used in this research were the adhered or overlapping and overlapping methods. The results of this research show that: (1) The compensation system in SME XYZ is still not fair and ideal based on the spread when compared to the minimum wage; (2) An appropriate and effective method for improving salaries for UKM XYZ is to use overlapping calculations.